Analyzing Essential Imports of Food and Inputs by Using Descriptive Analysis and Time Series Models (2002-2021) (Adjusted Exponential Smoothing Method) - Shammout, Amin Osama; Alsalaheen, Osama Suliman; Alzubaidi, Ameen Sulieeman (Journal of agricultural, environmental and veterinary sciences, 2023)
The main objectives of this study is to review the rates of self-sufficiency for the most important agricultural crops, and to estimate the growth of Jordan’s imports for the most prominent food commodities, including inputs of production factors during different time periods (2000-2011), (2011-2012). Ina addition general trend took place for analyzing and forecasting the imported quantities of agricultural commodities (21 were studied), including the most important inputs of agricultural production factors (4 were studied) by using the time series models. The results showed that the general trend of the aggregate imported food commodities is rising continuously with significant growth rates 8.03% and 8% respectively during the time period (2002-2011) and the period (2012-2021) , Therefore those rates are higher (3 times) of the population growth in Jordan which was about 2.4% year 2021. The study was also reviewed, the cost of energy consumption in agriculture sector is about 3.2% of the total energy costs consumed in Jordan. Note that the percentage of local production of energy to the total energy consumed in Jordan is about 2.5% in year 2020. The recommendation of this study focusses on rationalizing the local consumption of imported food commodities. Also, to develop programs stemming from national strategies in order to reduce waste, whether for food commodities such as cereals and flour, or inputs to production factors such as water and fertilizer in efficient use in the frame of resources allocation. It is also necessary to work on stimulating the establishment of water harvesting projects, as well as increasing investments pioneering projects in agricultural sector, including the expansion of existing projects through implementable policies and programs in providing technical and financial support for small and medium enterprises (SME’s) in the private sector.